Sandflies (Diptera: Psychodidae) from caves of the quartzite Espinhaço Range, Minas Gerais, Brazil - Ricardo Andrade Barata; Estefânia Conceição Apolinário (Memorias do Instituto Oswaldo Cruz, 2012)
This study investigated the sandfly fauna of two quartzite caves in the Espinhaço Mountain Range, located in the municipality of Diamantina, state Minas Gerais. From August 2010-July 2011, entomological sampling was performed in the caves of Salitre and Monte Cristo with two HP light traps exposed in the photic and aphotic zones of each cave. The sandfly fauna consisted of 17 species, among which Lutzomyia cipoensis was predominant (54.76%). The male/female ratio in the total captures was 1:2.5. The aphotic zone showed the highest frequency of specimens captured (65%). A greater density of sandflies occurred during the summer (January-February), coinciding with the period of higher temperatures, humidity and rainfall. The presence of Lutzomyia longipalpis, Lutzomyia whitmani and Lutzomyia pessoai, proven or suspected vectors of leishmaniasis, is of concern because the area is visited by many tourists.